Praktik Manajemen Laba dan Reaksi Pasar Setelah Event Pergantian Chief Executive Officer (CEO) - Juliartini, Desak Nyoman Sri; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 31 No 4 (2021)DO - 10.24843/EJA.2021.v31.i04.p01, 2021)
This research is to prove after the change of chief executive officer (CEO) of earnings management practices and market reaction. The total sample taken was using the nonprabability sampling method with a purposive sampling technique of 48 companies on the IDX which included the LQ45 index. The analysis technique used is simple linear regression and paired sample t-test on the DA and PER values of the company. Based on the results of the analysis found that there is no effect of earnings management on market reaction after one and two years of CEO turnover. These results prove that there is no important information on the announcement of CEO turnover, so it is less able to make significant stock price fluctuations. The next result is no difference in both earnings management and market reaction that occurs one and two years after CEO turnover. Keywords: Chief Executive Officer (CEO); Earning Management ; Market Reaction ; Price Earning Ratio (PER).